STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENDUKUNG PENINGKATAN HASIL BELAJAR SISWA DI SMA NEGERI 1 BANTAENG - Andy, Afriandi (TEKNOS: Jurnal Pendidikan dan Teknologi, 2023)
This research discusses the Teacher Strategy in Improving Student Learning Achievement in Islamic Religious Education Subjects in Bantaeng 1 High School, while the problems in this thesis are: (1) How is the strategy of Islamic religious education teachers in supporting the improvement of student learning achievement at Bantaeng 1 High School ? (2) What is the effectiveness of the teacher's strategy in supporting improving student learning achievement in Bantaeng 1 High School? To answer these problems, the type of research used is descriptive qualitative. Data sources from this study consisted of 1 Principal, 1 Deputy Principal of the Curriculum, 3 PAI teachers, and 15 students. The selection of the main data sources is done based on the analysis of data requirements needed by researchers. Data obtained through interviews, observations and documentation are then analyzed with data reduction techniques, data presentation and conclusions that follow the technical data analyst. The data validation technique is done by triangulation and member check. The results showed that the strategies undertaken by Islamic religious education teachers in supporting the improvement of student learning achievement in Bantaeng 1 High School were three namely contextual teaching learning strategies, the use of many methods, as well as individual and group strategies. The process of teaching and learning activities undertaken by the teacher by applying this strategy is based on the state of the student, the material being taught, the application of the method, the different types of student learning, as well as the various problems faced by students in learning. With the contextual teaching learning strategy, the use of many methods, as well as individual and group strategies used by effective Islamic religious education teachers in supporting the improvement of students' learning achievement in SMA Negeri 1 is proven by: the number of students who ask when the learning process takes place and the activeness of students in the classroom PAI learning is classified as good, feeling happy and motivated by the strategies used by PAI subject teachers to become better people, the value of daily assignments that on average the class achieves KKM completeness and the achievements achieved in religious competitions. From the results of this research, the advice that can be proposed is for all components of the madrasa, with an increase in student learning achievement in the PAI subjects, to maintain the strategies used and develop with various methods according to the title of the material being taught.